Transformative leadership and sustainable innovation in education : interdisciplinary perspectives - Baroudi, Sandra; Lytras, Miltiadis D. (Emerald Publishing Limited, 2024)
It is essential to learn what innovative practices and leadership approaches are adopted in the education sector to solve challenges such as digital transformations, inefficiencies in higher education administration models, and the need for a connection between innovation and sustainability within the curriculum. Transformative Leadership and Sustainable Innovation in Education addresses these topics, discussing several possible transformations at the policy, classroom, and research levels. Adopting an interdisciplinary approach, scholars from three main disciplines of education, business, and IT consider both a leadership and management perspective and an educational perspective. This integration of research, academia and industry bridges the gap between theory and practice, tackling how to make schools a sustainable enterprise, how to sustain student learning through leadership practices, and exploring the disruptive impact of artificial intelligence and other technologies on higher education. Transformative Leadership and Sustainable Innovation in Education is a valuable resource to a diverse network of policy makers, school and university leaders, educators, practitioners, curriculum designers, innovators, and investors who want to collaborate to identify and implement innovations that transform education and research.
Keywords: Educational leadership.; Transformative learning.; Sustainability.; Education -- Leadership.; Educational administration and organization.; Educational strategies and policy.; elektronické knihy; electronic books